Zygomatic implants : a finite element analysis study - Freedman, Michael (Trinity College (Dublin, Ireland). School of Dental Science, 2012)
Alveolar bone resorption commonly occurs following the loss of teeth in the posterior maxilla. The placement of conventional dental implants is often difficult in this area when resorption has occurred. Zygomatic implants may be placed into the zygomatic bone and can support a dental prosthesis in the severely resorbed edentulous maxilla.
Keywords: Dental Science, D.Ch.Dent.; D.Ch.Dent. Trinity College Dublin